ADDITIVE RATIO ASSESSMENT (ARAS) METHOD TO DETERMINE FURNITURE MATERIAL AT PT. CIREBON FURNITURE - Siti Ariani Rini; Mohamad Alif Wahidin; Virgiyanti; Muhammad Erwanto (PT. Berkah Digital Teknologi, 2024)
One of the manufacturers engaged in the furniture industry is Cirebon Furniture (CF) which is a leading company in the natural fiber & wood furniture industry. Making the right decisions based on the required standard categories requires comprehensive and accurate information, so that with sharp analytical skills, it is expected to produce decisions that are in accordance with the problem, namely by using several considerations. Such a method will be very risky for the progress of the furniture industry in the future, because the market image is declining on the quality of the furniture produced Therefore, a computer-based decision-making method is needed that can support decision making regarding the issue of selecting furniture material materials so that an effective and efficient production RAB decision can be obtained. Usage . With the conclusion of the method used by the previous research, namely the Additive Ratio Assessment (ARAS) method, the researcher proposed making a system and choosing the ARAS method to be implemented in this study, in order to help provide solutions in choosing decisions using the ARAS method as a weighting theory of each factor and real criteria in the prosecutor's office. Based on the problems that have been described, the author is interested in conducting research aimed at helping PT Cirebon Furniture in making decisions on determining furniture materials. Abstrak Salah satu produsen yang bergerak dibidang industri furniture yaitu Cirebon Furniture (CF) yang merupakan perusahaan terkemuka di industri mebel serat alam & kayu. Pengambilan keputusan yang tepat berdasarkan kategori standar yang diharuskan, diperlukan informasi-informasi yang menyeluruh dan akurat, sehingga dengan kemampuan analisa yang tajam, diharapkan dapat melahirkan keputusan- keputusan yang sesuai permasalahan yaitu dengan menggunakan beberapa pertimbangan. Cara seperti itu akan sangat beresiko untuk kemajuan industri meubel di masa yang akan datang, karena image pasar yang merosot terhadap kualitas furniture yang dihasilkan Oleh karena itu, dibutuhkan suatu metode pengambilan keputusan berbasis komputer yang dapat mendukung pengambilan keputusan menyangkut masalah pemilihan bahan material furniture sehingga dapat diperoleh keputusan RAB produksi secara efektif dan efisien. Penggunaan . Dengan adanya kesimpulan dari metode yang digunakan penelitian sebelumnya yaitu metode Additive Ratio Assessment (ARAS), maka peneliti mengusulkan pembuatan sistem dan memilih metode ARAS untuk di implementasikan dalam penelitian ini, guna dapat membantu memberikan solusi dalam memilih keputusan dengan menggunakan metode ARAS sebagai teori pembobotan dari setiap faktor dan kriteria nyata yang ada di kejaksaan. Berdasarkan permasalahan yang telah diuraikan, penulis tertarik untuk melakukan penelitian yang ditujukan untuk membantu PT Cirebon Furniture dalam mengambil keputusan penentuan material furniture.